CroNER: Recognizing Named Entities in Croatian Using Conditional Random Fields - Karan, Mladen; Glavaš, Goran; Šarić, Frane; Šnajder, Jan; Mijić, Jure; Šilić, Artur; Dalbelo Bašić, Bojana (Informatica)
CroNER: Recognizing Named Entities in Croatian Using Conditional Random Fields